Carbon and nutrient dynamics in landscapes under different levels of anthropogenic intervention in the semi-arid region of Brazil - Santos, Wilma Roberta dos; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Souza, Carlos André Alves de; Souza, Luciana Sandra Bastos de; Silva, Gabriel Ítalo Novaes da; Morais, José Edson Florentino de; da Silva, Marcelo José; Alves, Cleber Pereira; Montenegro, Abelardo Antônio de Assunção; Silva, Thieres George Freire da (Elsevier, 2024)
A mosaic of landscapes can be seen in the semi-arid region of Brazil as a result of anthropogenic activity (i.e. deforestation). These changes can lead to a reduction in soil carbon (C) and nutrient stocks, especially in arid and semi-arid regions. With this in mind, was evaluated both C and nutrient stocks dynamics in various landscapes in the semi-arid region of Brazil under different levels of anthropogenic intervention, including landscapes of preserved Caatinga (CAA), regenerating Caatinga (REGE) and deforested Caatinga (DEFA) located in the municipality of Floresta, Sertão of Pernambuco, and landscapes of the following forage cactus clones: ‘Orelha de Elefante Mexicana’ - Sertão (OEM-S), ‘Orelha de Elefante Mexicana’ - Agreste (OEM-A), and ‘IPA-Sertânia’ - Agreste (IPA-A) these last two located in the municipality of Pesqueira, Agreste of Pernambuco. Soil samples were collected at four depths (0–10, 10–20, 20–30 and 30–40 cm) and the physico-chemical (field capacity, bulk density, particle density, total porosity, sand, silt and clay) properties and stocks of C, P, K+, Ca2+, Mg2+ and Na+ were quantified. Data were analysed using the Kruskal-Wallis test and Conover-Iman mean test (for k samples) (p<0.05). The carbon stock was highest in forage cactus clone landscapes (OEM-A) with an average of 58.9 Mg ha−1, while the lowest stocks were observed in the CAA, DEFA and OEM-S landscapes with average values of 28.6, 23.74 and 23.3 Mg ha−1, respectively. Similarly, the highest P stock was recorded for OEM-A (0.4 Mg ha−1), while for the other landscapes P stocks were lower. The highest stocks of K+ were seen in REGE (0.90 Mg ha−1), while Ca2+ stocks showed no difference between CAA, REGE or OEM-A, with mean values of 6.5, 6.4 and 5.3 Mg ha−1, respectively. Therefore, in this study was found that stocks of C and nutrients decrease with increasing depth, so that these stocks tend to be higher during seasons when more water is available in the soil. Furthermore, the area that included the ‘Orelha de Elefante Mexicana’ clone in the Agreste region, showed a greater capacity for storing carbon and phosphorus.
Keywords: Dry forests; Forage cactus; Land use change; Stocks